(3GdJdNjU GdTGaj deJf GdcGaj aj Ydei GdYQhV hGdbhGais - (3UGdM Hf MSf GdaQVi GdMfHdis; (3TgGH GdOjf CHh GdYHGS CMeO Hf YHGO Hf TYjH GdUCHj GdbGgQj GdTGaYj, GdNhGU,J (B858 (3g` s ((3eQJVi Hf eUWai Hf MSf GdcQOi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg KbJi jbhd ef fXe PG GdYbO GdMSf GdMfHdi UGdM Hf MSf hHYO PG JdNjU eJf GdcGai ai Ydei GdYQhV hGdbhGai s
(3BNQgG (B:s
(3hGdMeO ddg Ydi NJGeI Ke UdGI Gddg eY SdGeg Ydi fHjg GdRci GdWGgQ hGdBd hGdUMH Phi GdeaGNQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3efXheI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdYQhV hGdbhGais